It's not always easy to buy the idea: strategies, perceptions, and implications of learner-centered teaching in coach education - Salles, William das Neves; Martins, Lincoln Cruz; Nascimento, Juarez Vieira do; Milistetd, Michel (Frontiers in Sports and Active Living, 2025)
IntroductionThe study aims to investigate the development of a learner-centered teaching (LCT), a constructivist-based proposal focused on the learner and the learning process, in a university-based coach education program (CEP) through an action research (AR) approach.MethodsParticipants were six students, the researcher and the professor of a Sport Pedagogy course of a public Brazilian university. The classes were taught in a collaborative way between the professor and the researcher, and rubrics were used to guide the LCT development process.Results and discussionThe proposal was developed gradually and progressively in the course, through diversified teaching strategies that prioritized student interaction and reflection. Facilitators were constantly concerned to ensure that students' perspectives and knowledge were valued during the construction of new teaching content, contributing to align the course with the LCT perspective. While at the beginning of the course the dimensions function of content and role of the teacher were emphasized, in subsequent classes greater attention was devoted to increasing students' responsibility for learning, balance the power between facilitators and students, and promote integrated, authentic assessment processes. To advance the investigated CEP, we recommend the LCT development in other courses of the program, enabling the consolidation of a curricular culture aligned to the constructivist perspective.